A community approach of pathogens and their arthropod vectors (ticks and fleas) in dogs of African Sub-Sahara - Heylen, Dieter; Day, Michael; Schunack, Bettina; Fourie, Josephus; Labuschange, Michel; Johnson, Sherry; Githigia, Samuel Maina; Akande, Foluke Adedayo; Nzalawahe, Jahashi Saidi; Tayebwa, Dickson Stuart; Aschenborn, Ortwin; Marcondes, Mary [UNESP]; et al. (Springer Nature, 2021)
Background: Arthropod-borne pathogens and their vectors are present throughout Africa. They have been well-studied in livestock of sub-Saharan Africa, but poorly in companion animals. Given the socio-economic importance of companion animals, the African Small Companion Animal Network (AFSCAN), as part of the WSAVA Foundation, initiated a standardized multi-country surveillance study. Methods: Macro-geographic variation in ectoparasite (ticks and fleas) and pathogen communities in dogs was assessed through molecular screening of approximately 100 infested dogs in each of six countries (Ghana, Kenya, Nigeria, Tanzania, Uganda and Namibia), both in rural and urban settings. The most important intrinsic and extrinsic risk factors within the subpopulation of infested dogs were evaluated. Results: Despite the large macro-geographic variation in the dogs screened, there was no consistent difference between East and West Africa in terms of the diversity and numbers of ticks. The highest and lowest numbers of ticks were found in Nigeria and Namibia, respectively. Most often, there was a higher diversity of ticks in rural habitats than in urban habitats, although the highest diversity was observed in an urban Uganda setting. With the exception of Namibia, more fleas were collected in rural areas. We identified tick species (including Haemaphysalis spinulosa) as well as zoonotic pathogens (Coxiella burnetti, Trypanosoma spp.) that are not classically associated with companion animals. Rhipicephalus sanguineus was the most abundant tick, with a preference for urban areas. Exophilic ticks, such as Haemaphysalis spp., were more often found in rural areas. Several multi-host ticks occurred in urban areas. For R. sanguineus, housing conditions and additional pets were relevant factors in terms of infestation, while for a rural tick species (Haemaphysalis elliptica), free-roaming dogs were more often infested. Tick occurrence was associated to the use of endoparasiticide, but not to the use of ectoparasiticide. The most prevalent tick-borne pathogen was Hepatozoon canis followed by Ehrlichia canis. High levels of co-parasitism were observed in all countries and habitats. Conclusions: As dogs share a common environment with people, they have the potential to extend the network of pathogen transmission to humans. Our study will help epidemiologists to provide recommendations for surveillance and prevention of pathogens in dogs and humans. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Amblyomma; Coxiella burnetii; Dog; Fleas; Haemaphysalis; Ixodes; Rhipicephalus; Sub-Sahara Africa; Ticks; Vector-borne pathogens